Cystic fibrosis. (May 2020) - Ewence, Alexandra E.; Jones, Andrew L.
Abstract: Cystic fibrosis (CF) is the most common autosomal recessive condition to affect white individuals. Defects in the CFTR chloride channel result in progressive organ dysfunction, particularly affecting the respiratory system. Patients require life-long care from multidisciplinary teams in specialist centres. Over time, improvements in screening and understanding of pathogenic alleles have increased diagnosis, while advances in management have led to better survival. The recent emergence of CFTR-modulating agents offers the potential to stabilize and improve lung disease, nutrition and quality of life in many people with CF.